Development of a downlight casing for a modern home design - Johansson, Thim; Nilsson, Linus (My University, 2022)
Lighting in newer homes today is not all about casting light upon the ordinary spaces in a dark room. Decoration lighting has become more of a thing that homeowners want to install to illuminate specific parts or objects. This report presents a product development project where the aim was to develop a casing for a new 230V downlight located on the window sill. The downlight will ease the installation work for the electrician since no LED driver is needed, and the downlight can be directly installed from the power supply. A market analysis was carried out to find the user needs of the electricians, and research regarding the different standards and regulations had to be carried out to fulfill the aims and requirements for the downlight. A prototype is the result of this project that complies with the customer’s needs and regulations from the IEC standards. It will go through the different requirements it has achieved and what is needed in the further development of this product.
Keywords: Keywords: Product development, downlight, concepts, illumination, market analysis.